Clinical assessment of two inlay-retained bridge designs in missing posterior teeth cases: a Randomized Clinical Trial - Soliman, Gomaa; Mahallawi, Omaima; Hamdy, Iman (Brazilian Dental Science, 2022)
Objective: This study aimed to evaluate the clinical performance of two inlay-retained bridge designs (proximal shaped and inlay shaped) in single missing posterior teeth cases. Material and Methods: A total of 70 cases with missing single posterior teeth were included in this study and divided into two groups with a 1:1 allocation ratio (n = 35 for each group). Group 1 (the control group): this group received an inlay retained bridge with inlay design on both abutments. Group 2 (the intervention group): this group received an inlay retained bridge with a proximal box on both abutments. PMMA resin (YAMAHACHI PMMA) was used for the try-in stage and monolithic zirconia (Katana, Kuraray) was used for the final restorations. The restoration surfaces were treated using sandblasting and Z-prime S (Bisco) and the cementation was done by using self-adhesive resin cement (Bisco). Fracture, marginal adaptation, postoperative sensitivity, caries, and gingivitis were assessed using the modified United States Public Health Service for restoration clinical assessments (MUSPHS standards) over 12 months of follow-up. Results: The results show there was no significant difference between the two groups. Kaplan-Meier survival curve was constructed to calculate the mean survival estimates of the two groups and we found that the two groups were clinically successful during a one-year follow-up. Conclusion: Both designs of inlay retained fixed dental prostheses revealed successful clinical performance in terms of Fracture, marginal adaptation, postoperative sensitivity, caries, and gingivitis. KEYWORDS Fracture; Inlay-retained fixed dental prosthesis; PMMA; Resin cement; Zirconia.